The Impact of Commodity Price Risk on Company Value - Empirical Analysis of Company Value Exposure to Commodity Prices - Salam, Aam Abdul; Novita, Neng Rahayu (Trunojoyo University of Madura, 2024)
Commodity prices tend to fluctuate more than exchange rates and interest rates, making commodity price risk a potentially larger source of risk for companies. This paper offers a detailed examination of the economic exposure to commodity prices for a broad group of nonfinancial firms. The findings reveal that some corporations have net exposure to specific commodity prices. However, despite the high volatility of commodity prices, the risk associated with them is not found to be more significant than other financial risks. The results suggest that commodity price changes have minimal impact on cash flow and that companies engage in hedging to manage this risk.